Spanish regional sheep systems: differences and evolution of sheep productivity - Ameen F.; Manrique E.; Olaizola A.M. (Changes in sheep and goat farming systems at the beginning of the 21st century : research, tools, methods and initiatives in favour of a sustainable development, 2009)
From the information provided by the National Farm Accountancy Data Network (FADN), referred to the sheep orientation for years 1987, 1990, 1994, 1999 and 2002 (added information of the sample of the sheep farms), the structural, economic and productive characteristics of representative meat and milk sheep systems of nine Spanish regions are described. Indices of animal productivity are elaborated (livestock capital), assimilable to the technical efficiency. For the considered regions, the differences in productivity, its evolution during the period 1987-2002 and its possible relationship with some characteristics of farms are analyzed. Considering that the productivity is a long term determinant of standard of living for sheep farmer, we try to advance a hypothesis related to sources of knowledge of this sector and role of technological change.
Proceedings of the Seminar of the Subnetwork on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2007/11/15-17, Ponte de Lima (Portugal)